Tree cover response to climate change in the forest-tundra of north-central Canada: fire-driven decline, not northward advance. Issue 2 (3rd April 2019) - Timoney, Kevin P.; Mamet, Steven D.; Cheng, Ryan; Lee, Peter; Robinson, Anne L.; Downing, David; Wein, Ross W.
ABSTRACT: Climate-vegetation models predict rapid northward advance of the subarctic forest-tundra in the coming century, although modelled responses may not be congruent with field data. This study aimed to determine how forest-tundra vegetation has responded to climate change in north-central Canada. Vegetation cover and gradients were mapped and compared to changes in climate parameters between 1955 and 2006. Increased aridity and annual and July warming corresponded to spatial isotherm shifts of one-half the width of the forest-tundra transition. Over the 51-year period, the areal extent of live trees decreased 26% (5227 km 2 ) while the areal extent of recently-burned trees increased 16-fold (7768 km 2 ). Changes in the areal extent of treeless wetland, tall shrubs, and upland tundra were non-significant. There was significant forest loss in the southern forest-tundra and modest forest gain in the northern forest-tundra. Overall, forest loss outpaced forest gain. The forest-tundra increased in areal extent by 6% via an overall broadening of the transition region. Contrary to model predictions, no appreciable northward migration of the forest-tundra was detected over the 51-year period despite significant climate change. Increased wildfire activity and moisture stress may limit the potential of tree vegetation to expand northward under a warming climate.